Manajemen Co-Production dalam Program Integrasi Pelayanan Kesehatan Primer (ILP) pada Posyandu Desa Tegalsari Selatan Kabupaten Jember - Devany, Aurel; Imanuari Pertiwi, Vidya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In order to organize and coordinate various primary health services with a focus on meeting health service needs based on the life cycle of individuals, families, and communities, the Ministry of Health of the Republic of Indonesia has issued a Minister of Health Decree on Technical Guidelines for the Integration of Primary Health Services. Primary Health Care Integration (ILP) is an effort to bring health services closer to the community, encompassing promotive, preventive, curative, rehabilitative, and/or palliative care. The village of Tegalsari in Jember Regency has implemented the ILP program at the Posyandu (community health post) and has established a management structure within the Posyandu. On the other hand, Tegalsari Village was selected as the representative of Jember District in the 2023 East Java Provincial Posyandu Competition. The inconsistency between the village's status as a Posyandu competition representative and the gaps in Posyandu management, particularly at the Posyandu in Southern Tegalsari Village as the venue for implementing the ILP program, creates a lack of alignment. This study aims to analyze and describe co-production management in the ILP program at the Posyandu in Tegalsari Selatan Village, Jember District. The research method uses a qualitative case study with purposive sampling to determine informants. The results show that five out of seven factors of co-production management theory have been fulfilled, so two factors—lay actor management and leadership—need to be improved. There is a need to strengthen the role of Posyandu cadres through continuous training with materials aligned with the dynamics of community health issues, as an effort to enhance the competencies of Posyandu cadres. This is because the selection of Posyandu cadres in the field does not yet align with existing regulations, and there is a shift in leadership style toward situational or transformational leadership.